Protective Effect of Low Molecular Weight Seleno-Aminopolysaccharide on the Intestinal Mucosal Oxidative Damage - Wen, Zheng-Shun (Mar Drugs, 2019)
Low molecular weight seleno-aminopolysaccharide (LSA) is an organic selenium compound comprising selenium and low molecular weight aminopolysaccharide (LA), a low molecular weight natural linear polysaccharide derived from chitosan. LSA has been found to exert strong pharmacological activity. In this study, we aimed to investigate the protective effect of LSA on intestinal mucosal oxidative stress in a weaning piglet model by detecting the growth performance, intestinal mucosal structure, antioxidant indices, and expression level of intracellular transcription factor nuclear factor erythroid 2-related factor 2 (Nrf2) and its related factors. Our results indicated that LSA significantly increased the average daily gain and feed/gain (p < 0.05), suggesting that LSA can effectively promote the growth of weaning piglets. The results of scanning electron microscope (SEM) microscopy showed that LSA effectively reduced intestinal damage, indicating that LSA improved the intestinal stress response and protected the intestinal structure integrity. In addition, diamine oxidase (DAO) and d-lactic acid (d-LA) levels remarkably decreased in LSA group compared with control group (p < 0.05), suggesting that LSA alleviated the damage and permeability of weaning piglets. LSA significantly increased superoxide dismutase (SOD), catalase (CAT), glutathione peroxidase (GSH-Px), and total antioxidant capacity (T-AOC) levels, but decreased malondialdehyde (MDA) level, indicating that LSA significantly enhanced the antioxidant capacity and reduced oxidative stress in weaning piglets. RT-PCR results showed that LSA significantly increased GSH-Px1, GSH-Px2, SOD-1, SOD-2, CAT, Nrf2, HO-1, and NQO1 gene expression (p < 0.05). Western blot analysis revealed that LSA activated the Nrf2 signaling pathway by downregulating the expression of Keap1 and upregulating the expression of Nrf2 to protect intestinal mucosa against oxidative stress. Collectively, LSA reduced intestinal mucosal damage induced by oxidative stress via Nrf2-Keap1 pathway in weaning stress of infants.